THE EFFECT OF EDUCATION LEVEL, POVERTY, AND ZIS FUND DISTRIBUTION ON ECONOMIC GROWTH IN EAST JAVA IN 2022 - Launiya, Khiyarotul; Siswahyudianto, Siswahyudianto (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research aims: This study aims to analyze the impact of education level, poverty, and the distribution of Zakat, Infak, and Sedekah (ZIS) funds on economic growth across districts and cities in East Java in 2022, both simultaneously and partially. Design/Methodology/Approach: A quantitative approach was applied using secondary data from 38 districts/cities in East Java. Saturated sampling (nonprobability sampling) was used to select the sample. Multiple linear regression analysis was conducted with SPSS version 27 after testing classical assumptions such as normality, multicollinearity, and heteroscedasticity. Research findings: The results show that education level, poverty, and ZIS fund distribution simultaneously have a significant positive effect on economic growth. Individually, each variable also significantly contributes to economic growth in the study area. Theoretical Contribution/Originality: This study contributes to human capital theory and the poverty trap theory by empirically examining how education, poverty, and ZIS funds influence economic growth in East Java. The finding that poverty positively affects economic growth offers new insights into the socioeconomic dynamics in regions with relatively high poverty rates. Practitioners/Policy Implications: The findings suggest that regional governments, BAPPEDA, BAZNAS, and policymakers should focus on improving education quality, productively reducing poverty, and optimizing ZIS fund distribution to promote sustainable and equitable economic growth. Research Limitations/Implications: This study is limited to data from 2022 and focuses only on education, poverty, and ZIS distribution, which may not capture all factors influencing economic growth. Future research should include additional variables and longer time periods for more comprehensive and generalizable results